Non-performing loans in the MENA region: How green growth mitigates the impact of climate risk - Khemiri, Mohamed Ali; Nouaili, Makram (Asian Economic and Financial Review, 2025)
The objective of this study is threefold. First, it examines the impact of climate risk (CRI) on credit risk, as measured by the ratio of non-performing loans (NPLs). Second, it investigates the effect of green growth (GGI) on NPLs. Third, it assesses whether GGI moderates the relationship between climate risk and NPLs. To achieve these objectives, the study utilizes a panel dataset of 40 traditional banks from Middle East and North Africa (MENA) countries, covering the years 2010 to 2022. The estimation employs the System Generalized Method of Moments (SGMM) estimator to address endogeneity and dynamic panel bias. Empirical results indicate that climate risk significantly increases the NPL ratio, leading to deterioration in credit quality under environmental stress. Conversely, green growth has a mitigating effect, significantly reducing credit risk among MENA banks. Additionally, the interaction between green growth and climate risk is negatively related to NPLs, suggesting that green growth can effectively shield bank credit portfolios from the adverse effects of climate risk. These findings have important implications for policymakers and financial institutions in the MENA region. Strengthening green growth policies can serve as a valuable tool to enhance banking sector resilience and promote sustainable financial development.